Effects of caregiver-provided individual cognitive interventions on cognition, social functioning and quality of life in older adults with major neurocognitive disorders: a systematic review. Issue 4 (April 2020) - Silva, Rosa; Bobrowicz-Campos, Elzbieta; Cardoso, Daniela; Costa, Paulo; Couto, Filipa; Camarneiro, Ana Paula; Abrunheiro, Sérgio; Almeida, Maria; Apóstolo, João
ABSTRACT: Objective: The objective of this review was to investigate the effectiveness of caregiver-provided individual cognitive interventions for improving cognition, social functioning and quality of life in older adults with major neurocognitive disorders. Introduction: A large number of people with major neurocognitive disorders live in their homes, requiring ongoing community care. Different individual cognitive intervention programs have been explored as a potential approach for implementation by caregivers on a one-to-one basis. These programs have the advantage of being implemented in a home setting and in the real-life context of the older adult, in a society that is increasingly aging and where aging in place is being fostered. Inclusion criteria: This review considered experimental studies that included older adults aged 60 years and over with major neurocognitive disorders who were receiving individual cognitive interventions (e.g. cognitive stimulation, cognitive training or cognitive rehabilitation) provided by their caregivers. The comparator was usual care, wait-list control or alternative therapeutic intervention. The primary outcomes of interest included cognition, social functioning and quality of life. Additionally, behavior, mood and activities of daily living were considered. Methods: A comprehensive search strategy was used to identify relevant published and unpublished studies from January 1995 to March 2018, written in English, Spanish and Portuguese. Studies meeting the inclusion criteria were retrieved and their methodological quality was assessed by two independent reviewers using the JBI critical appraisal checklists for randomized controlled trials and quasi-experimental studies. Quantitative data were extracted using the standardized data extraction tool from the JBI System for the Unified Management, Assessment and Review of Information. Due to the clinical and methodological heterogeneity in the included studies, statistical pooling was not possible. Therefore, findings are presented in a narrative format. Results: Eight randomized controlled trials and two quasi-experimental studies were included, with a total sample of 844 dyads (older adults and caregivers). The number of dyads included in the studies ranged from 16 to 356. Beneficial effects of the caregiver-provided individual cognitive interventions were observed in various cognitive domains, including memory, attention, verbal fluency and problem-solving. Two studies additionally reported the positive impact of the intervention of interest on general cognitive functioning. None of the reviewed studies revealed significant changes in quality of life. Social functioning was not analyzed in any of the included studies. Beneficial effects were also reported in relation to behavior and activities of daily living, despite the low level of evidence. Conclusions: This review responds to a gap in current international literature on the synthesis of evidence on the use of caregiver-provided individual cognitive interventions. The intervention of interest is associated with improvement in cognitive performance, revealing some benefits for the stabilization of neuropsychiatric symptoms and an increase in autonomy in activities of daily living. Further research on the impact of sociodemographic and clinical factors on the intervention effects is needed, as these factors seem to interfere with successful intervention implementation. To reinforce current evidence, the methodological quality of future studies should be improved.